THE EFFECT OF TRX EXERCISES TO IMPROVE ATTENTION CONCENTRATION AND SHOOTING ACCURACY FROM JUMPING FORWARD IN HANDBALL PLAYERS - Hayder Abbood Jaber (Proximus Journal Publishing, 2025)
The objective of the research is to determine TRX exercises that can enhance attention concentration and shooting accuracy in handball players by jumping forward. The researcher employed an experimental strategy, dividing participants into two groups: an experimental group and a control group. Pre- and post-measurements were utilized due to their alignment with the research's inherent qualities. The research sample was intentionally chosen from the players of Naft Misan Handball Club, consisting of 20 players who participated in the 2023 training season competitions. The sample size consisted of 20 players, who were randomly divided into two groups. The experimental group, consisting of 10 players, utilized total body resistance training (TRX). The control group consisted of 10 participants who underwent traditional exercises. Four players were selected for exploratory studies, and homogeneity measurements were conducted on basic variables such as age, height, weight, and training age. Parity was also assessed in certain physical abilities, including concentration of attention and accuracy of shooting from jumping forward among handball players. Utilizing the TRX attachment tool in junior handball training programs to implement total resistance training is highly successful in enhancing certain physical capabilities and skill performance. Encouraging coaches to incorporate total body resistance training (TRX) into handball training programs. The Iraqi Handball Federation will take action to organize seminars, workshops, and weight courses for coaches. These events will focus on highlighting the significance of incorporating total body resistance (TRX) training and providing guidance on managing training loads effectively.
Keywords: TRX Exercises; Attention Concentration; Shooting Accuracy